Aktivitas Antioksidan Ekstrak Etanol Kulit Biji dan Buah Bakau (Xylocarpus granatum J.Koenig) dengan Metode DPPH dan FRAP - Wardani, I Gusti Agung Ayu Kusuma; Adrianta, Ketut Agus; Udayani, Ni Nyoman Wahyu; Fridayana, Ni Luh Gede Erica; Mendra, Ni Nyoman Yudianti; Suena, Ni Made Dharma Shantini (Jurnal Ilmiah Medicamento, 2025)
Free radical compounds are molecules that possess reactive and unstable properties, which can damage biomolecules by disrupting the integrity of DNA, proteins and lipids. This condition can trigger oxidative stress, which can result in degenerative diseases. Humans require antioxidant intake from external sources when their own endogenous antioxidants are insufficient to counteract free radicals. Previous studies have demonstrated the high antioxidant activity of mangrove seeds. However, the antioxidant potential of mangrove seed coats and fruits remains underexplored, particularly when assessed using the DPPH and FRAP methods. This study aims to evaluate the antioxidant activity of seed coat and fruit extracts of Xylocarpus granatum J. Koenig using the DPPH and FRAP methods. This research is quantitative research with laboratory experimental approach. Antioxidant activity testing using DPPH and FRAP methods. Gallic acid was used as a comparison standard for antioxidant activity. The results obtained from the antioxidant activity testing of the ethanol extracts of seed shell, fruit and gallic acid were IC50 values of 10.83 mg/mL, 4.91 mg/mL and 0,793 mg/mL (DPPH) and RP50 of 4,455.63 mg/mL, 15,556.32 mg/mL and 34.04 mg/mL (FRAP). It is acknowledged that discrepancies in testing methodologies can influence the antioxidant activity of each extract, contingent on the nature of the free radical, the solvent, steric accessibility, and the pH of the medium.